Crystal plasticity constitutive model and thermodynamics informed creep-fatigue life prediction model for Ni-based single crystal superalloy - Lu, Pin; Jin, Xiaochao; Li, Pan; Sun, Yongle; Fan, Xueling (Elsevier, 2023)
Ni-based single crystal superalloys are the main constituent materials for aeroengine turbine blades. They are subjected to extensive in-service plastic deformation and creep-fatigue interaction, which can cause damage and failure and hence limit the turbine blade durability. In this study, a novel crystal plasticity-based constitutive model is proposed to predict the cyclic inelastic deformation of Ni-based single crystal superalloy under creep-fatigue loads, and the key aspects examined include cyclic strain hardening, ratcheting and stress relaxation behavior. The novelty of the model lies in the introduction of a dislocation density parameter in the kinematic hardening rule to describe the evolutionary characteristics of hysteresis loops. The constitutive model is implemented via the crystal plasticity finite element method and the predictions are in good agreement with experimental results. Furthermore, thermodynamic entropy generation is innovatively adopted as an indicator parameter for analysis of Ni-based single crystal creep-fatigue failure, and the corresponding creep and fatigue damage models are developed to evaluate the degree of damage. The half-life concept associated with the steady-state hysteresis loop is employed in the failure model to predict the creep-fatigue life without being limited by the computational efficiency of the crystal plasticity finite element method. The proposed model can well capture the characteristics of Ni-based single crystal creep-fatigue life, and the prediction falls within a scatter band of factor 2.0 compared to experimental results. The proposed creep-fatigue life prediction model is underpinned by deformation and failure mechanisms, which would provide a basis for accurate analysis and robust assessment of Ni-based single crystal superalloy performance and life.
Keywords: Crystal plasticity; Creep-fatigue interaction; Kinematic hardening; Entropy generation; Life prediction